2016
DOI: 10.1016/j.jrras.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of radionuclides concentration and average annual committed effective dose due to ingestion for some selected medicinal plants of South India

Abstract: Eight medicinal plants and soil samples from the Malnad area of Karnataka in South India (N 13 29 0 35.4 00 ; E 75 18 0 02.4 00) were analysed for activity concentrations of natural and artificial radionuclides using HPGe gamma spectrometry. The average annual committed effective dose (AACED) due to the ingestion of radionuclides from medicinal plants were also estimated. The activity concentrations of 226 Ra, 210 Pb, 232 Th, and 40 K were found to vary in the range of 32.27e60.12 Bqkg À1 , 56.09e160.56 Bqkg À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 11 publications
3
18
5
Order By: Relevance
“…In this study, the average radioactivity concentration of 232 Th in medicinal plants was found as 61.15 Bqkg -1 which is much higher than previously reported in other countries 2,6,14 . Similarly, 40 K concentrations in medicinal plants were higher than concentration in medicinal plants from other countries except India and Egypt 2,6 .…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…In this study, the average radioactivity concentration of 232 Th in medicinal plants was found as 61.15 Bqkg -1 which is much higher than previously reported in other countries 2,6,14 . Similarly, 40 K concentrations in medicinal plants were higher than concentration in medicinal plants from other countries except India and Egypt 2,6 .…”
Section: Resultscontrasting
confidence: 63%
“…Similarly, 40 K concentrations in medicinal plants were higher than concentration in medicinal plants from other countries except India and Egypt 2,6 . These results can be explained may be due to a wide differences in the soil component which are normally directly dependent to the main rocks, the type of weathering processes, and also the content of the fertilizers used in the soil 2 .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Medicinal plants as intercrops are gaining interest in both developing and developed countries and can provide a novel strategy for sustainable agricultural cropping systems (Chandrashekara and Somashekarappa 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of the average annual committed effective dose (AACED) due to ingestion of NORMs in coffee can be calculated using the following equation (Njinga et al, 2015;Chandrashekara and Somashekarappa, 2016):…”
Section: Average Annual Committed Effective Dose or Dose Ingested By mentioning
confidence: 99%